2016
DOI: 10.1097/iae.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator for Subfoveal Hemorrhage Due to Age-Related Macular Degeneration

Abstract: Treatment with tPA improves the functional and anatomical outcomes in patients with thick subfoveal hemorrhage due to subfoveal choroidal neovascular membrane secondary to exudative age-related macular degeneration and was superior to PD without tPA. Vitrectomy with subretinal tPA injection reduced the final disciform scar compared with PD with or without intravitreal tPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…30 Studies by Fujikawa et al, Mizutani et al, and Fassbender et al looked at the effects of tPA in patients with submacular hemorrhage, and results were mixed with it not making a difference, increasing the chance of a rebleed, or helping with visual outcome respectively. 21,22,29 Our study was unique in that patients in the pneumatic ± tPA group received their pneumatic displacement and intravitreal tPA in a staged process so the effects of each step could be observed. Most patients in the pneumatic ± tPA group in our study returned after intravitreal injection of C3F8 and had not yet had sufficient displacement of their hemorrhage (16 of 18 patients).…”
Section: Discussionmentioning
confidence: 99%
“…30 Studies by Fujikawa et al, Mizutani et al, and Fassbender et al looked at the effects of tPA in patients with submacular hemorrhage, and results were mixed with it not making a difference, increasing the chance of a rebleed, or helping with visual outcome respectively. 21,22,29 Our study was unique in that patients in the pneumatic ± tPA group received their pneumatic displacement and intravitreal tPA in a staged process so the effects of each step could be observed. Most patients in the pneumatic ± tPA group in our study returned after intravitreal injection of C3F8 and had not yet had sufficient displacement of their hemorrhage (16 of 18 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have reported the efficacy of a vitrectomy and subretinal tPA for SMH [ 5 ]. Fassbender et al reported that the PPV/tPA/SF 6 showed a better outcome than PD only (changes of mean BCVA were −0.90 vs. +0.10 logMAR units) [ 22 ]. Treumer et al treated SMH patients with a PPV, a subretinal tPA and anti-VEGF [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, intravitreal injection of tPA and gas has been found to be safe and effective in clinical trials in terms of displacing submacular clots and improving visual acuity [17,[37][38][39]. Some recent reports [40][41][42] even suggest that intravitreal injection of tPA and gas without vitrectomy may be as effective in reducing blood volume as submacular injection of tPA with vitrectomy.…”
Section: Discussionmentioning
confidence: 99%